Subtle and Overt Behaviors Toward Ethnic Minority Leaders and the Moderating Role of Competence. (August 2019) - Anderson, Amanda J.; Ahmad, Afra Saeed; King, Eden B.; Gilrane, Veronica
This study extends research on stereotypes and leadership to consider the subtle and overt behavioral responses to leaders from multiple ethnic backgrounds. Specifically, the study focuses on overt and subtle discrimination toward African American, Asian American, Middle Eastern American, and White male leaders. Results from an experiment measuring authentic reactions to leaders reveal that Asian American leaders were treated more negatively in comparison to White and Middle Eastern American leaders. Furthermore, individuating information about the leader's competence marginally improved performance expectations of Middle Eastern American leaders compared with White and Asian leaders. However, African American leaders were treated less positively when information about competence was provided compared with when it was not. The findings suggest that the unique stereotypes of each ethnic group can affect the utility of providing individuating information about competence.